S73 Neutrophil sub-types across lung diseases. (12th November 2019) - Thulborn, SJ; Cane, J; Downs, M; Connolly, C; Borg, C; Gittins, A; Hynes, G; Talbot, N; Bafadhel, M; Pavord, I
Abstract : Introduction and objectives: Neutrophilic inflammation is a key component of many chronic lung diseases including COPD, asthma and cystic fibrosis. Despite progress in the treatment of eosinophilic airways disease neutrophilic inflammation still requires a deeper understanding of underlying biology to aid treatment development. Recent studies have identified three types of neutrophils present in broncho-alveolar lavage; banded, segmented and hypersegmented. Hypersegmented neutrophils have been shown to be elevated in patients with airways disease and linked to a reduction in lung function. 1 We aimed to determine if these subtypes could be identified in the sputum of patients with three distinct lung diseases and how they differ between disease types and healthy controls. Method: Sputum samples from 24 patients with airways disease (10 asthmatics, 10 COPD and 4 CF) and 7 healthy controls was collected. Sputum was processed as per standard protocol. Neutrophils were classified based on morphology into segmented (2–4 clearly defined lobes), banded (1 lobe) and hyper-segmented (>4 lobes). Results: We were able to identify each sub-group of neutrophil in the sputum of the 4 different groups analysed. There are distinct differences in the distribution of these sub-types of neutrophils (Segmented p=0.016; Banded p=0.008; Hyper-segmented p=0.070), specifically between segmented and banded neutrophils across the 4 groups (figure 1). COPD had significantly less banded neutrophils (p=0.008) and more hypersegmented neutrophils (0.060) than healthy controls. Conclusion: There is a variation in neutrophil sub-groups in sputum across lung diseases and healthy controls. COPD patients have significantly lower proportions of immature banded neutrophils perhaps suggesting a distinct activating environment. Reference: Lokwani, R., et al ., Hypersegmented airway neutrophils and its association with reduced lung function in adults with obstructive airway disease: an exploratory study. BMJ Open, 2019. 9(1): p. e024330.